Flexible Sigmoidoscopy in the PLCO Cancer Screening Trial: Results From the Baseline Screening Examination of a Randomized Trial - Weissfeld, Joel L.; Schoen, Robert E.; Pinsky, Paul F.; Bresalier, Robert S.; Church, Timothy; Yurgalevitch, Susan; Austin, Joseph H.; Prorok, Philip C.; Gohagan, John K. (JNCI : Journal of the National Cancer Institute, 2005)
Background: The Prostate, Lung, Colorectal and Ovarian (PLCO) cancer screening trial is a randomized clinical trial to test the effectiveness of cancer screening, including the effect of flexible sigmoidoscopy screening on colorectal cancer mortality. Here we report findings from the baseline screening flexible sigmoidoscopy examination. Methods: Analyses included 77 465 men and women aged 55–74 years who were enrolled at 10 screening centers. The trial administered baseline risk factor questionnaires, offered 60-cm flexible sigmoidoscopy examinations, referred patients with screen-detected colorectal polyps or masses to personal physicians, and tracked subjects with polyps or masses to determine results from diagnostic follow-up. Cochran–Mantel–Haenszel statistics and logistic regression were used to test for differences in proportions according to sex and age. Results: A total of 64 658 subjects (83.5%) underwent screening flexible sigmoidoscopy, and at least one polyp or mass was identified in 15 150 subjects (23.4%). Of these, 74.2% received follow-up lower endoscopic procedures. Follow-up lower endoscopy was more frequent in subjects with at least one larger (≥0.5 cm) polyp or mass (86.0% [95% confidence interval CI = 84.6% to 87.4%] and 81.0% [95% CI = 79.8% to 82.2%] in women and men, respectively) than in those with a smaller (<0.5 cm) polyp or mass (69.1% [95% CI = 67.5% to 70.6%] and 65.4% [95% CI = 64.1% to 66.7%] in women and men, respectively). The yields per 1000 screened, depending on 5-year age group, were as follows: for colorectal cancer, 1.1–2.5 in women and 2.4–5.6 in men; for advanced adenoma, 18.0–30.4 in women and 36.1–49.1 in men; and for colorectal cancer or any adenoma, 50.6–79.6 in women and 101.9–128.6 in men. Approximately 77% (130/169) of the colorectal adenocarcinoma patients were stage I or II at diagnosis. Conclusions: Acceptance of screening flexible sigmoidoscopy was high. Diagnostic follow-up varied according to polyp size, yet cancer or adenoma detection rates met expectations.